Current Aquaculture of the Eastern Oyster Crassostrea virginica and Its Potential for Innovative Technology in Florida - Emily Caffrey; Joshua Patterson; Ruth Francis-Floyd; Roy P. E. Yanong (EDIS)
This publication provides information on the status of oyster fisheries and aquaculture in Florida as well as general information about how oysters are grown in agricultural and restoration systems. It then introduces a series of technologies that have been developed in other US states and in other countries, strategies that may have utility in Florida. Finally, it covers some specifics of the permitting process as it relates to oyster aquaculture in Florida.